The profile of students’ metacognition in solving analytic geometry: Gender and cognitive style perspective - Muhammad Ridlo Yuwono; Septiana Wijayanti (Universitas Islam Negeri (UIN) Mataram, 2018)
[English]: This case study aimed to describe the metacognition of male students in solving analytical geometry problems referring to cognitive style. The subjects were mathematics students who enrolled in Analytic Geometry course and selected by purposive sampling technique. The instrument of this research was the researcher as the main instrument and a problem-solving test as the supporting instrument. Data were collected using a think-aloud method and analyzed through three steps: reducing data, presenting data, and drawing conclusions. The results of this study show that at the stage of understanding the problem, FI and FD male students read questions silently and did not write what is known and asked in the problem. At the planning stage, FD male student drew elements that are fully known, while male FI students did not do so. At the stage of implementing the plan, FI male student was aware of less effective strategy, while FD male students did not. In re-checking phase, FI male student used a variety of strategies and checked whether or not the results meet the criteria of solving the problem, while FD male students used a variety of strategies but are assisted with a prompt. This study shows that FI and FD male students have similar metacognition profile at the stage of understanding the problem, but they are different in planning, doing the plan and re-checking the result of problem-solving. Keywords : Metacognition, Gender, Analytic geometry, Cognitive style, Problem-solving [Bahasa]: Peneltian studi kasus ini bertujuan untuk mendiskripsikan metakognisi mahasiswa laki-laki dalam memecahkan masalah geometri analitik ditinjau dari gaya kognitif. Subjek penelitianadalah mahasiswa matematika yang mengambil mata kuliah Geometri Analitik dipilih dengan teknik purposive sampling. Instrumen penelitian meliputi instrumen utama (peneliti) dan instrumen bantu (soal pemecahan masalah geometri analitik). Data dikumpulkan dengan menggunakan metode think aloud. Analisis data dilakukan dengan cara reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan pada tahap memahami masalah, mahasiswa laki-laki FI dan FD membaca soal dalam hati serta tidak menuliskan yang diketahui dan ditanyakan. Pada tahap menyusun rencana, mahasiswa laki-laki FD menggambar unsur-unsur yang diketahui secara lengkap, sedangkan mahasiswa laki-laki FI tidak melakukannya. Pada tahap melaksanakan rencana, mahasiswa laki-laki FI menyadari terdapat strategi yang kurang efektif, sedangkan mahasiswa laki-laki FD tidak melakukannya. Pada tahap mengecek kembali, mahasiswa laki-laki FI menggunakan strategi bervariasi dan mengecek apakah hasil yang diperoleh memenuhi kriteria yang digunakan untuk memecahkan masalah, sedangkan mahasiswa laki-laki FD menggunakan strategi yang bervariasi tetapi dibantu dengan pertanyaan. Penelitian ini menunjukkan bahwa mahasiswa laki-laki FI dan FD memiliki profil metakognisi yang sama pada tahap memahami masalah namun berbeda pada menyusun rencana, melaksanakan rencana dan mengecek kembali hasil pemecahan masalah. Kata kunci: Metakognisi, Gender, Geometri analitik, Gaya kognitif, Pemecahan masalah